An Analysis of the Malassezia Species Distribution in the Skin of Patients with Pityriasis Versicolor in Chengdu, China. (10th August 2014) - Xie, Zhen; Ran, Yuping; Zhang, Hao; Zhang, Min; Wan, Huiying; Li, Conghui
Abstract : Pityriasis versicolor (PV) is a common clinical problem associated with Malassezia species ( Malassezia spp.). Controversies remain regarding the specific species involved in the development of PV. This study analyzed the difference in Malassezia spp. distribution in lesional and nonlesional skin in Chinese PV patients. A paired design was applied. Lesional and nonlesional scales from 24 cases were collected; real-time fluorescence quantitative PCR was used to detect 10 different Malassezia spp. In lesional skin, the highest detection rates were for M. globosa (95.8%), M. restricta (91.7%), and M. sympodialis (50.0%). In nonlesional skin, the highest detection rates were for M. globosa (87.5%), M. restricta (79.2%), and M. dermatis (33.3%). A significant difference in the detection rate was only found for M. sympodialis (50.8% versus 20.8%, P = 0.04 ) . Compared with nonlesional skin, the amount of M. globosa, M. restricta, and M. sympodialis in lesional skin was significantly higher ( 3.8 ± 1.3, 2.5 ± 1.1, and 3.2 ± 1.6 times higher, resp.). The results of this study do not indicate that M. globosa and M. restricta are directly correlated with PV development; however, M. sympodialis is more likely related to PV development in Chinese individuals.